2014
DOI: 10.1074/jbc.m114.580357
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Dysfunction Activates Autophagy and the Keap1-Nrf2 Pathway

Abstract: Background: Malfunctions in the ubiquitin-proteasome system cause accumulation of non-functional, potentially toxic protein aggregates. Results: The protein aggregates activate Nrf2 and are then excluded by autophagy in vivo. Conclusion: Both Nrf2 and autophagy serve as in vivo cellular adaptations to impaired proteasome. Significance: Cells contain networks of cellular defense mechanisms against defective proteostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 41 publications
(34 reference statements)
4
86
0
Order By: Relevance
“…To explain the synergistic control of Dronc protein levels by the UPS and autophagy, we considered that, because the UPS and autophagy are mechanistically linked, impairment of the UPS can enhance autophagy, which is often referred to as compensatory autophagy 1,[19][20][21][22][23][24][25][26][27] (reviewed by Park and Cuervo, 3 Wojcik 28 and Lamark and Johansen 29 ). For example, in Drosophila, compensatory autophagy after proteasome impairment has been reported in neurons, in fat body cells and in adult flies.…”
Section: Simultaneous Inactivation Of Both the Proteasome And Autophamentioning
confidence: 99%
See 1 more Smart Citation
“…To explain the synergistic control of Dronc protein levels by the UPS and autophagy, we considered that, because the UPS and autophagy are mechanistically linked, impairment of the UPS can enhance autophagy, which is often referred to as compensatory autophagy 1,[19][20][21][22][23][24][25][26][27] (reviewed by Park and Cuervo, 3 Wojcik 28 and Lamark and Johansen 29 ). For example, in Drosophila, compensatory autophagy after proteasome impairment has been reported in neurons, in fat body cells and in adult flies.…”
Section: Simultaneous Inactivation Of Both the Proteasome And Autophamentioning
confidence: 99%
“…16 The incorporation of Atg8 fusion proteins (for example, with green fluorescent protein (GFP) and/or mCherry) into autophagosomes is often used as a marker for autophagosomes 17 and autophagic flux. 18 Although it was initially assumed that the UPS and autophagy are independent of each other, recent evidence has suggested that there is crosstalk and feedback between the two 1,[19][20][21][22][23][24][25][26][27] (reviewed by Park and Cuervo, 3 Wojcik 28 and Lamark and Johansen 29 ). This is mostly due to the observation that autophagy can also degrade ubiquitylated proteins.…”
mentioning
confidence: 99%
“…The ubiquitin-proteasome system and autophagy are crucial for maintaining the proteostasis and are interdependent pathways. In mice with reduced proteasome activity in their livers, proteasome dysfunction activated autophagy and KEAP1/NRF2 pathway [58]. Recently, NRF2 has been identified as a regulator of autophagy gene expression [59] indicating its potential in regulating cellular proteostasis (Figure 1).…”
Section: Nrf2 Modulation Of Proteostasis Oxidative Stress and Inflammentioning
confidence: 99%
“…During this process, as BHMT are normally highly enriched on the membranes of autophagosomes or their precursors, 51,52 they are passively packaged into autophagosomes and subsequently processed. In the absence of the cargo receptors, aggresomes cannot form, 52,53 thereby abolishing the MAP1LC3-mediated autophagosome formation and the parallel sequestration of BHMT. Many other possibilities exist and many questions remain, including whether and how the multimeric BHMT are preferentially associated with autophagosome membranes, that need to be further addressed in the future.…”
Section: Different Mechanisms Mediate Starvation-and Proteasome Inhibmentioning
confidence: 99%
“…Further, cargo receptors SQSTM1 and NBR1 not only recognize and bind to ubiquitinated proteins, but are also required for their assembly into aggregate-like structures (aggresomes) that are important for their subsequent recognition and sequestration by the MAP1LC3-containing autophagosome structures, as supported by the findings that loss of SQSTM1 significantly suppresses the accumulation of ubiquitinated proteins as well as the formation of inclusion bodies both in autophagy-deficient neurons and hepatocytes, and also in hepatocytes with impaired proteasome activity that otherwise show elevated levels of ubiquitinated aggregates. 53,54 Given these observations, one putative scenario is that upon proteasomal impairment, cargo receptors SQSTM1 and NBR1 recruit ubiquitinated proteins into aggresomes, a prerequisite step for their recognition by the MAP1LC3-containing membranes that subsequently assemble into mature autophagosomes. During this process, as BHMT are normally highly enriched on the membranes of autophagosomes or their precursors, 51,52 they are passively packaged into autophagosomes and subsequently processed.…”
Section: Different Mechanisms Mediate Starvation-and Proteasome Inhibmentioning
confidence: 99%